1983
DOI: 10.1111/j.1365-3091.1983.tb00702.x
|View full text |Cite
|
Sign up to set email alerts
|

Turbidite depositional patterns and flow characteristics, Navy Submarine Fan, California Borderland

Abstract: The late Pleistocene and Holocene stratigraphy of Navy Fan is mapped in detail from more than 100 cores. Thirteen 14C dates of plant detritus and of organic‐rich mud beds show that a marked change in sediment supply from sandy to muddy turbidites occurred between 9000 and 12,000 years ago. They also confirm the correlation of several individual depositional units. The sediment dispersal pattern is primarily controlled by basin configuration and fan morphology, particularly the geometry of distributary channels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
201
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 322 publications
(210 citation statements)
references
References 9 publications
9
201
0
Order By: Relevance
“…Other factors must be contributing to this fining-upward trend. Piper and Normark (1983) demonstrated that when a turbidity current is thick relative to the channel depth it can overtop the levee, stripping off the upper part of the flow and allowing the residual coarser portion of the flow to continue down channel. This process, termed "flow stripping," occurs when thick turbidity flows travel in channels having sharp bends.…”
Section: Channel Leveesmentioning
confidence: 99%
See 1 more Smart Citation
“…Other factors must be contributing to this fining-upward trend. Piper and Normark (1983) demonstrated that when a turbidity current is thick relative to the channel depth it can overtop the levee, stripping off the upper part of the flow and allowing the residual coarser portion of the flow to continue down channel. This process, termed "flow stripping," occurs when thick turbidity flows travel in channels having sharp bends.…”
Section: Channel Leveesmentioning
confidence: 99%
“…Flow density, and consequently velocity within the channel on the other hand, may increase if sediment is eroded from the channel floor and added to the turbidity current load. Denser, faster turbidity currents will also tend to become thinner, decreasing the potential to export sediment overbank (Piper and Normark, 1983). Turbidity currents traveling several hundreds of kilometers downfan must then continuously maintain a balance between flow thickening and dilution by entrainment, and increase in flow concentration by flow stripping and erosion.…”
Section: Channel Leveesmentioning
confidence: 99%
“…Similar stages of channel drift have been recognised in other submarine sinuous channel systems (Peakall et al 2000;Lien et al 2003). In the final stage, spillover deposits overtop the channel levees (Piper & Normark 1983). In the Mangarara case, no evidence for levees has been observed.…”
Section: Position Of Outcrop Occurrences Within a Channel-fan Systemmentioning
confidence: 67%
“…The right-hand levees are higher and broader than the left-hand levees in the north hemisphere, this being controlled by the Coriolis force deflecting the turbidity currents to the right. The centrifugal force associated with flow stripping processes is responsible for the preferential building of sediment waves at the outer corners of bends of the levees (Piper and Normark, 1983). The upper-middle fan boundary is the result of the disappearance of the channel-levee systems due to the progressive downpath decrease of the fine-grained fraction in sediment transported by the channelised flows.…”
Section: Fan Modelmentioning
confidence: 99%
“…The difficulty of coring and the very low penetration of the 3.5 kHz seismic waves does not make the study of such environment easy. The transition from a muddy channel-levee system on the upper fan to flat-lying sand lobes on the middle and lower fan, represents a facies shift related to particle sorting and segregation due to channel-levee overflow as shown in the Amazon Fan (Flood and Piper, 1997), Mississippi Fan (Bouma, 1985), Navy Fan, (Piper and Normark, 1983).…”
Section: Fan Modelmentioning
confidence: 99%